Perancangan Sistem Plambing Air Bersih Pada Gedung Menara BRI Pekanbaru - Anza, Nuri; Asmura, Jecky; Andesgur, Ivnaini (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Plumbing as a procurement of sanitation facility is a control system of environment impact through piping planning, for supplying clean water and drainage of waste water in a building without causing pollution. The steps of design has consisted of preliminary study in the form of literature studying, collecting and processing data, drawing and determining a budget plan. This study shows that clean water needs is 41.412 liters/day. The diameter of the used pipes are 1 inches, 1Â¼ inches, 2 inches, 2Â½ inches, 3 inches, 4 inches. Keywords: Plumbing, supplying clean water